RANCANG BANGUN APLIKASI PENDUKUNG PENGAMBILAN KEPUTUSAN PENYELEKSIAN CALON SISWA BARU - Risma Miftahul Ulum, Ade; Mardiana, Ardi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The acceptance of new student is one of processes within educational institutions like school which is used to select candidate according to stated criteria by related school. Generally, the process of acceptance of new student began with registration, selection, and announcement steps of new student. This research was taken place at SMPN 1 Kasokandel which during the time has practiced the acceptance of new student manually or computerized but used Microsoft Office Excel only. It caused lack data, mistake within measurement because of manually mark measurement. Fundamental problem of this research is how to install information system for acceptance of new student at SMPN 1 Kasokandel that make information representation accurately and efficiently. therefore the author intends to create a new application-based student admission information system using the java programming language and MySQL database.